CODE SWITCHING USED IN CONVERSATIONS BY AN AMERICAN STUDENT OF THE DARMASISWA PROGRAM - Retnawati, Saptina; Mujiyanto, Yan (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2015)
This study analyzes code switching used in conversations by an American student of the darmasiswa program, addressing four objectives to find out the types and the functions of code switching, the possible factors that cause the occurence of code switching, and the impacts of code switching to the abilities of involved languages.The approach of this study is qualitative. The researcher applies mixed techniques to obtain data; recording the conversations in natural setting and interview. The analysis is interpretive.The findings of this study indicate that three types of code switching found in the conversations; intersentential code switching, intrasentential code switching, and tag/emblematic switching. They are used for various functions due to several reasons. The most significant function is to emphasize the message which gets the highest percentage (27.6%) and intention to clarify the speech content to the other interlocutors is the most significant factor causing code switching whichgets highest percentage (40.8%).It is found that code switching gives impact to the abilities of involved languages in conversations. It results in the loss of English language ability and the gain of Indonesian language ability.